Levels and trends of synthetic musks in marine bivalves from French coastal areas. (April 2021) - Aminot, Yann; Munschy, Catherine; Héas-Moisan, Karine; Pollono, Charles; Tixier, Céline
Abstract: The levels and trends of four bioaccumulative synthetic musks (galaxolide - HHCB, tonalide - AHTN, musk xylene - MX and musk ketone - MK) were investigated in filter-feeding bivalves collected yearly since 2010 at sites of contrasted pressure along the French coasts. Quantification rates were high for all 4 compounds (85–99%), indicating their geographical and temporal extensive occurrence in the French coastal environment. The polycyclic musks HHCB and AHTN prevailed, with median concentrations of 2.27 ng g −1 dw and of 0.724 ng g −1 dw, whilst nitromusks were found 1 to 2 orders of magnitude lower. These levels were in the high range of those encountered for various other CEC families at the same sites and comparable to those from other locations on European coasts. Unlike for the other musks, the accumulation of HHCB was evidenced to be species-specific, with significantly lower levels found in oysters in comparison with mussels, possibly suggesting a higher metabolization in oysters. Geographical differences in musk distribution highlighted the sites under strong anthropogenic pressures and these differences were found to be consistent between years. The HHCB/AHTN ratio proved to be discriminant to explain the relative occurrence of polycyclic musks. The 8-year time series showed that only the now-banned compound MX displayed a significant decrease in most sites, whilst stable concentrations of the other musks suggested consistency in their usage over the last decade. These results provide reference data for future studies of the occurrence of personal care products on European coasts. Highlights: Investigation of synthetic musks in bivalves from French coasts in 2010–2019. Widespread occurrence of HHCB, AHTN, musk xylene and ketone. Species-specific accumulation of HHCB, potentially related to metabolization. Levels reflect urban pressure, notably in the Seine Bay. Significantly decreasing temporal trend for musk xylene only.